René Coulomb y Emilio Duhau (coords.) La ciudad y sus actores. México : UAM-Azcapotzalco, 1988. 200 p. - Muñoz Contreras, María Elena (Estudios Demográficos y Urbanos, 1989)
RENÉ COULOMB y EMILIO DUHAU (coords.), La ciudad y sus actores, UAM-Azcapotzalco, México, 1988.